Aktivitas Antioksidan dan Total Fenolik Se’i Sapi yang dicuring Menggunakan Ekstrak Etanol Kulit Buah Naga Merah (Hylocereus polyrhizus) - Yustina Seuk; Paulus Klau Tahuk; Kristoforus W. Kia (JAS, 2020)
The purpose of this research is to find out the antioxidant activity, total phenolic, moisture content and the pH of Se'i cow that is riered using red dragon fruit skin ethanol extract. The variables measured in this study are antioxidant activity, total phenolic, moisture content and the pH of se'i cows. The ingredients used in this study are beef back thigh parts and red dragon fruit skins. The method used is complete random design with variations of the following treatment: R0 = beef + seasoning, R1 = Beef + Seasoning + Nitrat 25 mg, R2 = Beef + Seasoning + Red Dragon Fruit Peel Extract 50%, R3 = Beef + Seasoning + Red Dragon Fruit Peel Extract 60%. Based on the results of this study can be concluded that the greater the addition of Red Dragon fruit peel extract, the greater also the antioxidant activity and total phenolic se'i and will decrease the moisture content and the pH of Se'i cow. Where the value of IC50 on R3 treatment is 207.853 ppm and the total phenolic of 1.068 mg/g while the moisture content of R3 is 44.829% and has a pH value of 5.21.